Learners’ views on the use of Case-Based Learning and ICT in business English speaking - Ria, Tiara Nove; Hartono, Rudi; Wahyuni , Sri (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
This study aims to explore students' perceptions of the integration of Case-Based Learning (CBL) and information and communication technology (ICT) in teaching speaking skills in the English for Business course. Using a qualitative approach, the study was conducted at STIE Semarang involving 25 undergraduate students taking the course. Data were collected through semi-structured interviews and reflective journals to understand how students experience, interpret and evaluate the use of real business cases supported by digital technology in their speaking activities. The results showed that the majority of students perceived the ICT-based CBL approach as an interesting, contextualized method that helped improve their confidence and communicative skills. In addition, the use of ICT was considered to facilitate collaboration, provide authentic materials, and enable more flexible learning. However, challenges were also found, such as limited digital literacy and unequal participation in group work. The study concludes that the integration of CBL and ICT can create a dynamic and contextualized ESP learning environment that supports language development and critical thinking skills.